The not-just-anybody family - Byars, Betsy Cromer; Rogers, Jacqueline (New York : Delacorte Press, 1986)
With a young brother in the hospital, a grandfather in jail, and their mother traveling with a rodeo, Maggie and Vern try to settle family problems.
690
Accelerated Reader AR
Keywords: Brothers and sisters -- Fiction; Family problems -- Fiction